1959
DOI: 10.1152/jappl.1959.14.6.966
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and cerebral circulatory control during exercise at .21 and 2.0 atmospheres inspired pO2

Abstract: Respiratory and cerebral hemodynamic responses to leg exercise during respiration of air at 1.0 atm. and O2 at 2.0 atm. were studied in relation to changes in arterial and internal jugular venous blood oxygen composition, pH, pCO2 and bicarbonate concentration. The hyperpnea of exercise at 1.0 atm. was accompanied by arterial and venous acidemia and hypocapnia. Oxygen administration during exercise at 2.0 atm. lowered ventilation, restored arterial pH and pCO2 toward resting levels and caused venous pCO2 to ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

1962
1962
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…They concluded that arterial blood rather than tissue Pco 2 controlled flow, while noting that a vasoconstriction produced by O 2 could have masked a dilation associated with tissue hypercapnia. They reaffirmed this in a subsequent study during exercise (8). Ledingham,Harper and McDowall (9) have shown that if Paco 2 is held constant, the administration of O2 at 3 atm to dogs resulted in no significant change in cerebral cortical blood flow determined by krypton clearance.…”
Section: Severinghaus Lassenmentioning
confidence: 81%
“…They concluded that arterial blood rather than tissue Pco 2 controlled flow, while noting that a vasoconstriction produced by O 2 could have masked a dilation associated with tissue hypercapnia. They reaffirmed this in a subsequent study during exercise (8). Ledingham,Harper and McDowall (9) have shown that if Paco 2 is held constant, the administration of O2 at 3 atm to dogs resulted in no significant change in cerebral cortical blood flow determined by krypton clearance.…”
Section: Severinghaus Lassenmentioning
confidence: 81%
“…In the first four studies CBF was determined over a 10-minute period, by the continuous sampling modification of the nitrous oxide method (6). The "syringe integration" sampling procedure was first suggested by Schienberg and Stead (7).…”
Section: Methodsmentioning
confidence: 99%
“…Determinations of whole blood metabolic gas composition and N20 content were performed manometrically in duplicate as described elsewhere (6). Percentage oxygen saturation of hemoglobin was estimated from the manometrically measured values after corrections for physically dissolved oxygen and, in addition, for hemoconcentration in the determination of the oxygen capacity (12,13).…”
Section: Methodsmentioning
confidence: 99%
“…Measurements have included ventilation, oxygen consumption, carbon dioxide elimination, and both end-tidal and arterial gas tensions (51,53). Ensuing experiments demonstrated hypercapnia at rest (91), but to a greater extent during exercise (11, 25, 40 -42, 52, 74, 89 -91, 107, 118).…”
mentioning
confidence: 99%
“…Another study failed to find an effect of PO 2 on arterial PCO 2 between 0.7 and 1.3 ATA during immersed prone exercise at 4.7 ATA (8). Factors besides respiratory drive attenuation that may contribute to the reduction in exercise ventilation include peripheral chemoreceptor inhibition and attenuation of the acidemia that occurs during heavy exercise (51).…”
mentioning
confidence: 99%